Supraphysiological effects of pancreatic polypeptide on gastric motor function and nutrient tolerance in humans. Issue 17 (26th August 2021) - Verbeure, Wout; Rotondo, Alessandra; Janssen, Pieter; Carbone, Florencia; Tack, Jan
Abstract: Pancreatic polypeptide (PP) is known to affect food intake. In this exploratory study, we set out to investigate its supraphysiological effect on food tolerance, gastric accommodation, and emptying. In 12 healthy volunteers, 0, 3, or 10 pmol*kg −1 *min −1 PP was administered intravenously (PP0, PP3 or PP10). Thirty minutes thereafter, nutrient drink infusion (60 ml*min −1 ) through a nasogastric feeding tube was started until maximum satiation. Gastric accommodation was assessed by measuring the intragastric pressure (IGP; nasogastric manometry). In a separate test, the effect of PP0 or PP10 on gastric emptying was tested in 10 healthy volunteers and assessed using the 13 C breath test. Results are presented as mean ± SEM, and p  < 0.05 was considered significant. For the IGP test, PP increased ingested nutrient volume: 886 ± 93, 1059 ± 124, and 1025 ± 125 ml for PP0, PP3, and PP10, respectively ( p  = 0.048). In all groups, Nadir IGP values were reached upon food intake (transformed values: 1.5 ± 0.2, 1.7 ± 0.3, and 1.6 ± 0.3 mmHg for PP0, PP3, and PP10, respectively; NS) to return to baseline thereafter. For the gastric emptying study, volunteers ingested a similar nutrient volume: 802 ± 119 and 1089 ± 128 ml ( p  = 0.016), and gastric half‐emptying time was 281 ± 52 and 249 ± 37 min for PP0 and PP10, respectively (NS). No significant correlation between tolerated nutrient volume and IGP drop (R² < 0.01; p  = 0.88 for PP0 vs. PP3 and R² =0.07; p  = 0.40 for PP0 vs. PP10, respectively) or gastric half‐emptying time (R² = 0.12; p  = 0.32) was found. A supraphysiological PP dose enhances food tolerance; however, this effect is not mediated through gastric motility. Clinical Trial registry number: NCT03854708 is obtained from clinicaltrials.gov. Abstract : In this exploratory study, we set out to investigate the supraphysiological effect of pancreatic polypeptide on food tolerance, gastric accommodation, and emptying. Interestingly, this dose enhances the tolerated amount of an infused meal, which is contradictory with literature using physiological dosages. The effect was not mediated through gastric motility.